PENGARUH PENGGUNAAN ECU RACING TERHADAP KINERJA SEPEDA MOTOR 4 LANGKAH 150 CC DENGAN VARIASI OKTAN BAHAN BAKAR PERTAMAX - Devangga Rizqi Fardhana; Ranto Ranto; Husin Bugis (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
Technological advances in the automotive sector have made the automotive industry issue an injection ignition system that uses the ECU which makes ignition timing and fuel injection more precise. In this study, the replacement from the standard ECU to the Racing ECU was carried out with variations in Pertamax RON 92 and RON 98 fuels, which is expected to increase the power and torque of the engine. The research showed that use of the Standard ECU and use the Pertamax 98 fuel had more effect on torque. While, use the ECU Racing and Pertamax 98 fuel has more effect on vehicle power.